Sensory Templates and Manager Cognition Art, Cognitive Science and Spiritual Practices in Management Education - Springborg, Claus (Palgrave Studies in Business, Arts and Humanities,, 2018)
This book explores the role of art and spiritual practices in management education. It takes recent developments in cognitive science relating to the metaphorical and embodied nature of cognition as its starting point. Introducing the concept of 'sensory templates', Springborg demonstrates how managers unconsciously understand organizational situations and actions as analogous to concrete sensorimotor experiences, such as pushing, pulling, balancing, lifting, moving with friction, connecting and moving various substances. Real-life management and leadership case studies illustrate how changing the sensory templates one uses to understand a particular situation can increase managerial efficiency and bring simple solutions to problems that have troubled managers for years. Sensory Templates and Manager Cognition will be of interest to scholars and students of managerial cognition, leadership and neuroscience, as well as practising managers and management educators.